Keeping food on the table: Urban food environments in Nairobi under COVID-19 - Chege, Christine G. Kiria; Mbugua, Mercy M.; Onyango, Kevin; Lundy, Mark M. (Bioversity International and the International Center for Tropical Agriculture, 2021)
The COVID-19 pandemic has spread rapidly around the world since late 2019. Measures taken to curb infection rates—curfews, border closures, closure of markets, and movement restrictions—have disrupted food systems and affected food environments. There is limited evidence of the effects of the pandemic on food environments, especially in the informal neighborhoods/slums of urban towns or cities. This study characterizes the food environment (formal and informal outlets) in low- and middle-income urban neighborhoods of Nairobi, Kenya during the current COVID-19 pandemic. It also analyses the social economic effects of government measures, taken to curb the pandemic, on different types of food outlets in these communities.